Effect of Supplementation of Slow Release Non-Protein Nitrogen Compound on the Lactation of Cows - Gadegaonkar, G.M.; Patil, M.B.; Gulvane, S.U.; Karambele , N.R.; Jagadale, S.D. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A feeding trial to study the effect of slow release non-protein nitrogen compound was conducted for 180 days in twelve early lactating Gir and crossbred cows that were divided into two equal groups viz., T0 (Control) and T1 (treatment). T0 received farm made concentrate mixture and T1 received concentrate mixture containing 1% SRNPN (Slow release non-protein nitrogen compound). The animals in both the groups were fed mixed hay as dry roughage and paragrass as green roughage. Dry matter intake in T0 and T1 was comparable. The average daily milk yield, 4% FCM yield, TDN and DCP intake of cows inT1 was significantly (P
Keywords: Slow release non-protein nitrogen (SR-NPN); Concentrate Mixture; Lactating Cow; Digestibility of Nutrients; Milk Yield; Milk Composition